Improving gonorrhoea molecular diagnostics: Genome mining-based identification of identical multi-repeat sequences (IMRS) in Neisseria gonorrhoeae - Shiluli, C.; Kamath, S.; Kanoi, B.N.; Kimani, R.; Maina, M.; Waweru, H.; Kamita, M.; Ndirangu, I.; Abkallo, Hussein M.; Oduor, Bernard; Pamme, N.; Dupaty, J.; et al. (Elsevier, 2024)
Background Curable sexually transmitted infections (STIs), such as Neisseria gonorrhoeae (N. gonorrhoeae), are a major cause of poor pregnancy outcomes. The infection is often asymptomatic in pregnant women, and a syndrome-based approach of testing leads to a missed diagnosis. Culture followed by microscopy is inadequate and time-consuming. The gold standard nucleic acid amplification tests require advanced infrastructure settings, whereas point-of-care tests are limited to immunoassays with sensitivities and specificities insufficient to accurately diagnose asymptomatic cases. This necessitates the development and validation of assays that are fit for purpose.